2015
DOI: 10.1111/zoj.12256
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and molecular phylogeny of the Neotropical genusAtlantoscia(Oniscidea, Philosciidae): DNA barcoding and description of two new species

Abstract: Identification to the species level using morphology is challenging when usual diagnostic characters are similar amongst related taxa. Within the Neotropical genus Atlantoscia, differences between nominal species are generally small and restricted to a few characters. Despite the power of DNA sequencing to identify and distinguish between species, molecular phylogenies of terrestrial isopods from the Neotropics have not been determined. In this study, two new species of Atlantoscia were described and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…As pointed out previously, Atlantoscia species are morphologically similar and the diagnostic characteristics traditionally used to delimit species are few and subtle (Campos-Filho et al 2013;Zimmermann et al 2015). Despite this similarity, the respiratory areas on the pleopod exopods of In addition to the morphological evidence, molecular analysis with both mitochondrial and nuclear genes also showed that the Atlantoscia and Paratlantoscia comprise distinct and well supported clades with a high genetic divergence between them.…”
Section: A New Genus Of Terrestrial Isopods Described By Means Of Intmentioning
confidence: 94%
See 3 more Smart Citations
“…As pointed out previously, Atlantoscia species are morphologically similar and the diagnostic characteristics traditionally used to delimit species are few and subtle (Campos-Filho et al 2013;Zimmermann et al 2015). Despite this similarity, the respiratory areas on the pleopod exopods of In addition to the morphological evidence, molecular analysis with both mitochondrial and nuclear genes also showed that the Atlantoscia and Paratlantoscia comprise distinct and well supported clades with a high genetic divergence between them.…”
Section: A New Genus Of Terrestrial Isopods Described By Means Of Intmentioning
confidence: 94%
“…The authors demonstrated that using integrative taxonomy by coupling morphology and DNA sequences is an efficient strategy for delimitation of Atlantoscia species and to investigate their relationships. However, some issues still persist For instance, Atlantoscia rubromarginata Araujo & Leistikow, 1999 and Atlantoscia ituberasensis Campos-Filho, Lisboa & Araujo, 2013 are quite different from the other congeneric species and thus might not belong to this genus (Zimmermann et al 2015). Specifically, they are genetically and geographically distant and possess unique and specialized morphologies, with well developed respiratory areas in the pleopods (Campos-Filho et al 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, our knowledge of the diversity of terrestrial isopods from Brazil has increased considerably and, to date, ca 200 species are known, including species from the subterranean environment (Schmalfuss 2003;Araujo & Quadros 2005;Souza et al 2006Souza et al , 2010Souza et al , 2011Souza et al , 2015Araujo & Taiti 2007;Sokolowicz et al 2008;Campos-Filho & Araujo 2011a, 2011bCampos-Filho et al 2012, 2013a, 2013b, 2015a, 2015b, 2016, 2017a, 2017b, 2017cCosta et al 2014;Zimmermann et al 2015;Cardoso et al 2016).…”
Section: Introductionmentioning
confidence: 99%